The importance of microsonics concept for optimization of endodontic retreatment outcome: a case report - Cláudia Fernandes de Magalhães Silveira; Carlos Eduardo Fontana; Felipe Davini; Roberta Aranha de Araújo Arruda; Carlos Eduardo da Silveira Bueno (Revista Sul-Brasileira de Odontologia, 2013)
During the past few decades, the endodontic treatment has benefited from the development of new techniques and devices, which have improved the outcome and predictability. Important attributes such as the operating microscope and ultrasonics have found indispensable applications in a number of dental procedures in endodontics. Objective and case report: This study describes a case of endodontic retreatment of a maxillary first molar in which the second mesiobuccal canal could be located by extending the access to the mesial direction further than usual and by a closer inspection of the pulp chamber floor. Conclusion: The “microsonics concept” has enhanced the quality of endodontic treatment and retreatment, becoming increasingly more useful in applications such as localization of root canal orifices.